Upaya Menciptakan Pembelajaran Bahasa Arab Yang Bermutu (Studi Atas Pembelajaran Bahasa Arab Di Lembaga Kursus Bahasa Arab “Al-Farisi” Pare) - Ratna Sa’idah (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2017)
Learning Arabic Language actually will never be separated from the last goal ofIslam education which is being usedas a tool to understand Islam values inside Islam primary values resource that is Al-Qur'an and Al-Hadits along with turats books and all of those are written in Arabic language. Right now,learning Arabic Language in Indonesia arenot exist at formal institution only, there is a lot non-formal institution where everyone can learn Arabic Language, one of them are Al-Farisi. This Arabic Language course institution doing some effort to escalate the creation of qualified Arabic Language learning on their curriculum,learning strategy, learning media, also learning evaluation. One of important thing to remember is they only work with lecturers who graduate from Al-Farisi.